Comparative efficacy of perioperative lidocaine infusion versus thoracic epidural analgesia for pain management in abdominal surgery: systematic review and meta-analysis - Gustavo R.M. Wegner; Bruno F.M. Wegner; Ramon Huntermann; Manoela L. Pinto; Júlia A.P. Vieira; Amanda P. de Souza; Francisco J.L. Bezerra (Brazilian Journal of Anesthesiology)
Background: Recent randomized clinical trials have compared the perioperative use of Intravenous (IV) lidocaine and Thoracic Epidural Analgesia (TEA) for postoperative analgesia in patients undergoing abdominal surgery. Methods: A systematic search was conducted on Embase, Web of Science (all databases), Cochrane Library, and PubMed on March 25, 2024, adhering to the Cochrane Handbook and PRISMA guidelines. Results: Out of 1261 screened studies, 6 were included. TEA provided superior pain relief on a 0 to 10 pain scale at rest compared to IV lidocaine at 2 (n = 335, MD = -0.72, 95% CI -0.19 to -1.25, p = 0.007423, I2 = 83%) and 24 hours postoperatively (n = 402; MD = -0.18, 95% CI -0.12 to -0.23; p < 0.000001, I2 = 18%). However, no statistically significant differences were observed on pain scores at rest at 48 and 72 hours. TEA provided superior pain relief on a 0 to 10 pain scale during coughing at 24 hours postoperatively (n = 360; MD = -0.36, 95% CI -0.19 to -0.52, p = 0.000019, I2 = 2%), but no statistically significant differences were observed in pain scores on coughing at 48 and 72 hours. There were no statistically significant differences in postoperative nausea and vomiting, time to first flatus, or length of hospital stay. Conclusions: TEA provides more effective postoperative pain relief compared to IV lidocaine during the first postoperative day, as evidenced by analyses of pain both at rest and during coughing.